Photoplethysmography: A measure for the function of the autonomic nervous system in focal impaired awareness seizures. (25th July 2020) - El Atrache, Rima; Tamilia, Eleonora; Mohammadpour Touserkani, Fatemeh; Hammond, Sarah; Papadelis, Christos; Kapur, Kush; Jackson, Michele; Bucciarelli, Bethany; Tsuboyama, Melissa; Sarkis, Rani A.; Loddenkemper, Tobias
Abstract: Objectives: Photoplethysmography (PPG) reflects variations of blood perfusion in tissues, which may signify seizure‐related autonomic changes. The aim of this study is to assess the variability of PPG signals and their value in detecting peri‐ictal changes in patients with focal impaired awareness seizures (FIASs). Methods: PPG data were recorded using a wearable sensor placed on the wrist or ankle of children with epilepsy admitted for long‐term video‐electroencephalographic monitoring. We analyzed PPG data in four different periods: seizure‐free, preictal, ictal, and postictal. Multiple features were automatically extracted from the PPG signal—frequency, duration, amplitude, increasing and decreasing slopes, smoothness, and area under the curve (AUC)—and were used to identify preictal, ictal, or postictal changes by comparing them with seizure‐free periods and with each other using a linear mixed‐effects model. Results: We studied PPG in 11 patients (18 FIASs), including seizure‐free, preictal, and postictal periods, and a subset of eight patients (12 FIASs) including the ictal period. Compared to the seizure‐free period, we found significant changes in PPG (1) during the ictal period across all features; (2) during the preictal period in amplitude, duration, increasing slope, and AUC; and (3) during the postictal period in decreasing slope. Significance: Specific PPG changes can be seen before, during, and after FIASs. The peri‐ictal changes in the PPG features of patients with FIASs suggest potential applications of PPG monitoring for seizure detection.